Genetic Diversity of Pleurotus Ostreatus Using Random Amplification Polymorphisms DNA Technique - Al-Yassiry, Zahraa A.N.; Jebor, Mohammed Abdullah (International Journal of Scientific Research in Biological Sciences, 2024)
— Mushrooms are the reproductive structures of large fungi that do not have leaves or tissues containing chlorophyll. Nevertheless, they continue to increase in size and generate fresh organic matter on an annual basis. Mushrooms provide high nutritional value and can be consumed as food, tonic, and medicinal substances. They include a high amount of crude fibre, proteins, and beneficial vitamins, while having a low content of fat and calories. They have many therapeutic benefits. The edible King Oyster mushroom (i.e. Pleurotus ostreatus) is part of the genus Pleurotus, which is regarded significant. Using various molecular techniques, genetic variation amongst several strains of wild macrofungi could be documented and expressed. This work examined the relatedness and genetic diversity of Pleurotus ostreatus from various locations. To determine the genetic diversity of P. ostreatus, a random amplified polymorphic DNA-polymerase chain reaction marker was used. 6 of the 21 bands produced by two primers (OPL-03 and OPI-05), which indicated variability between the isolates examined, were polymorphic and ranged in size from 250 to 1 kb. The phylogenetic analysis for two primers used in this study led to classification into three clusters, the first includes PO1 and the second cluster includes PO8 and the third major cluster contained 3 classes (first class includes PO7 second class PO9 and third class contains PO3, PO4, PO2, PO5and PO6. Conclusions Genetic diversity and genetic relatedness of the examined wild P. ostreatus were revealed by RAPD. This will enhance the selection of strains for additional utilizations and documentations.